A3 receptor agonist, Cl-IBMECA, potentiate glucose-induced insulin secretion from MIN6 insulinoma cells possibly through transient Ca2+ entry - Mohammad Keyvanloo Shahrestanaki; Mahmoud Aghaei (Wolters Kluwer Medknow Publications, 2019)
Diabetes incidence showed ascending trends in recent years indicating urgent need for new therapeutic agents. Extracellular adenosine signaling showed promising results. However, role of its A3 receptor in pancreatic β-cells proliferation and insulin secretion is not well established. Thus, we aimed to determine its main signaling mediators in MIN6 insulinoma cell line. A3 adenosine receptor (A3AR) expression was confirmed using RT-PCR. Receptor functionality was evaluated by measurements of cAMP, using ELISA kit, and intracellular Ca2+ levels, using Fura 2/AM probe in response to the specific A3AR agonist (Cl- IBMECA). Insulin ELISA kit was used to measure insulin release. Herein, we mentioned that MIN6 cells express active form of A3AR, which decreased cAMP levels with the half maximal effective concentration (EC50) value of 5.61. [Ca2+]i Levels transiently (approximately 120 sec) increased in response to the agonist. Cl-IBMECA increase insulin secretion at 0.01-1 μM, but showed an inhibitory effects at higher concentrations (1-10 μM). Altogether, we found that in MIN6 cells, A3AR, possibly through Ca2+ mediated signaling pathways, potentiated glucose-induced insulin secretion.